2022
DOI: 10.1186/s12873-022-00717-2
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic attitudes towards prehospital spinal care: a cross-sectional survey

Abstract: Background The optimal application of spinal motion restriction (SMR) in the prehospital setting continues to be debated. Few studies have examined how changing guidelines have been received and interpreted by emergency medical services (EMS) personnel. This study surveys paramedics’ attitudes, observations, and self-reported practices around the treatment of potential spine injuries in the prehospital setting. Methods This was a cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
4
0
2
Order By: Relevance
“…The few published studies that have surveyed providers on changing standards have documented support for evolving guidelines and enthusiasm for moving beyond strict requirements and toward flexible approaches 13,50 . Respondents to a recent survey within this service have documented a belief that SMR is seen as less important than in the past as well as some skepticism toward the effectiveness, importance, and applicability of SMR 51 . Participants noted the discomfort that standard SI/SMR causes patients and reported consciously choosing smaller collars or alternative positioning to avoid aggravating patients, choices that reflect an underlying tension between balancing the need to adhere to protocols with that of providing care to diverse patients in unpredictable situations 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few published studies that have surveyed providers on changing standards have documented support for evolving guidelines and enthusiasm for moving beyond strict requirements and toward flexible approaches 13,50 . Respondents to a recent survey within this service have documented a belief that SMR is seen as less important than in the past as well as some skepticism toward the effectiveness, importance, and applicability of SMR 51 . Participants noted the discomfort that standard SI/SMR causes patients and reported consciously choosing smaller collars or alternative positioning to avoid aggravating patients, choices that reflect an underlying tension between balancing the need to adhere to protocols with that of providing care to diverse patients in unpredictable situations 51 .…”
Section: Discussionmentioning
confidence: 99%
“…51 Participants noted the discomfort that standard SI/SMR causes patients and reported consciously choosing smaller collars or alternative positioning to avoid aggravating patients, choices that reflect an underlying tension between balancing the need to adhere to protocols with that of providing care to diverse patients in unpredictable situations. 51 The data collected in this study illustrate these patterns. The significant increase in the proportion of high-acuity patients implies that patients with minor injuries or low-risk MOIs have received SI/SMR less frequently over time.…”
Section: Discussionmentioning
confidence: 99%
“…Um deles se refere à divergência da terminologia, conformidade com as diretrizes e a implementação por parte das equipes 21 . Outra pesquisa realizada em um serviço pré-hospitalar no Canadá mostrou que equipes são céticas em relação a vários elementos do protocolo de RMC, contudo, acabam utilizando algumas estratégias para equilibrar a adesão ao protocolo com a otimização do cuidado durante os atendimentos 22 .…”
Section: Discussionunclassified
“…One refers to the divergence of terminology, compliance with the guidelines, and implementation by the teams 21 . Another study carried out in a pre-hospital service in Canada showed that teams are skeptical about various elements of the SMR protocol but use some strategies to balance adherence to the protocol with optimizing care during visits 22 .…”
Section: Discussionmentioning
confidence: 99%